2008
DOI: 10.1007/s00103-008-0508-7
|View full text |Cite
|
Sign up to set email alerts
|

Depressionen im Alter

Abstract: Depression is the most frequent psychiatric disorder in old age. Some patients have had depressive episodes or other psychological disorder in an earlier part of their life span. Older people show more somatic or cognitive complaints compared to younger depressives. Risk factors for depression in old age are (incident) physical disorders, sleep disorders or loss of spouse. Depression worsens course and prognosis of comorbid somatic disorders. A major consequence is the high suicide rate in the elderly. Depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 37 publications
0
5
0
7
Order By: Relevance
“…For aging people, depression is one of the most common psychiatric disorders [ 16 ]. Several studies have indicated that depressive symptoms were important predictors of QOL in the elderly [ 12 , 17 – 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…For aging people, depression is one of the most common psychiatric disorders [ 16 ]. Several studies have indicated that depressive symptoms were important predictors of QOL in the elderly [ 12 , 17 – 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…5 Depression is one of the most frequent psychiatric disorders in old age. 6 A survey of 4,265 Chinese adults aged 60 and older showed that the prevalence of depressive symptoms for empty nest elderly adults was 8.18%, significantly higher than that for those who are not empty nesters. 7 Factors such as being female, being single, and having poor self-rated health and life status were reported to be associated with depression.…”
Section: China's Empty Nest Elderly Need Better Carementioning
confidence: 99%
“…De nombreux facteurs de risques peuvent être traités de m anière préventive, en particulier les troubles du sommeil persistants, l'isolement ou la pauvreté. Les résultats thérapeutiques et les perspectives de succès sont tout aussi bons que pour des personnes plus jeunes [10].…”
Section: Dépressionunclassified